2022
DOI: 10.3389/fpsyt.2021.813130
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in COVID-19 Lockdown Impact on Mental Health of Undergraduate Students

Abstract: Background: Prolonged university closures and social distancing-imposed measures due to the COVID-19 pandemic obliged students to at-home learning with online lectures and educational programs promoting potential social isolation, loneliness, hopelessness, and episodes of clinical decompensation.Methods: A web-based cross-sectional survey was carried out in a university institute in Milan, Northern Italy, to assess the COVID-19 lockdown impact on the mental health of the undergraduate students. We estimated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 38 publications
9
40
0
1
Order By: Relevance
“…A total sample of N = 9261 full answers was gathered through the Google Forms platform, composing bachelor’s students, master’s students, PhD students, teaching staff, and administrative personnel, aged ≥18 years old. General data and descriptive statistics from the same survey were previously published in two scientific papers [ 31 , 42 ]. To ensure sample homogeneity and reduce biases, in the present study, only the student sub-population was selected for the analysis, including bachelor’s, master’s, and PhD students.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total sample of N = 9261 full answers was gathered through the Google Forms platform, composing bachelor’s students, master’s students, PhD students, teaching staff, and administrative personnel, aged ≥18 years old. General data and descriptive statistics from the same survey were previously published in two scientific papers [ 31 , 42 ]. To ensure sample homogeneity and reduce biases, in the present study, only the student sub-population was selected for the analysis, including bachelor’s, master’s, and PhD students.…”
Section: Methodsmentioning
confidence: 99%
“…In the third section, the architectural parameters were clustered into: Other variables were analyzed through the survey, such as: access to livable outdoor spaces (balcony or garden) measured in terms of balcony depth and garden access. If the respondent had access to outdoor spaces, natural daylight exposure of outdoor spaces was assessed in terms of hours per day; such variables are not pertinent for this paper, and were previously analyzed and discussed in a scientific publication by the authors [31,42].…”
Section: Survey Questionnairementioning
confidence: 99%
“…Only some showed that buildings, like residential living situations, impacted people's physical and mental well-being during the epidemic (67)(68)(69). Some analyzed the effect of housing built-environments on personal depression and anxieties (70,71). Also, studies using multiple regression analyses show that the better the building design is, the fewer stress people may feel and the more active feedback the user will get (72).…”
Section: Discussionmentioning
confidence: 99%
“…It also has been demonstrated that, as a basis for the restorative effects of the environment, preferences moderate the effect of perceptions of green space on positive emotion (56). After experiencing the COVID-19 lockdown, university students were more eager to be in outdoor environments (35,57). The positive attitude toward being outside may have an impact on students' perceived naturalness and landscape preference, which may affect their positive emotions about enjoying the CGSs.…”
Section: The Mediate E Ect Of Landscape Preferencementioning
confidence: 99%